COVID-19 pandemisinde tıp fakültesi öğrencilerinde algılanan stres ve nomofobi - Aktaş Terzioğlu, Merve; Toker Uğurlu, Tuğçe (Journal of Dependence, 2021)
Objective: This study aimed at investigating the stress levels of medical students during the COVID-19 pandemic and their fear of being deprived of their mobile phones (nomophobia). Method: An online questionnaire consisting of the Perceived Stress Scale (PSS), Nomophobia Scale (NMP-Q) and sociodemographic data was completed with the participation of 341 students. Results: The use of smartphones increased during the COVID-19 pandemic andthis increase was statistically similar in both sexes. According to NMP-Q results, 67% of females were mildly, 32.1% were moderate, and 0.9% were severe nomophobic. Of the males 55% were mildly, while 39.3% were moderate, and 5.7% were found to be severe nomophobic. It was determined that the mean PSS scores of males were significantly higher than females. Mean scores of PSS and NMP-Q for students aged 20 and under were found to be similar to those of students over 20. There was a positive correlation between PSS scores and all dimensions of NMP-Q. Conclusion: Medical faculty students were found to be mild/moderate level nomophobic. During the COVID-19 pandemic, male medical students were more affected than female students, they felt greater stress, and had a higher tendency toward nomophobia.